Description of “Jigsaw Reading” Activity in Reading Classes - Kochkorova Zulfizar Abduxamid qizi; Rakhmadjonova Irodakhon Ilkhomovna (Journal of Innovation in Education and Social Research, 2023)
Reading is a part of four language skills that we know. It is an activity that has to do in our daily lives. It can be as a tool for gathering information and to get knowledge, most of knowledge and science are found from the books. So, how can we get information and knowledge if we do not read books?